COMPORTAMENTO DE ÍONS METÁLICOS EM SOLOS, SEDIMENTOS ÁGUAS SUPERFICIAIS E SUBTERRÂNEAS NO CÓRREGO DA ANTA, S.J. DO RIO PRETO-SP - Hypolito, Raphael; Nascimento, Silvia Cremonez (Águas Subterrâneas, 2004)
RESUMO A determinação e o monitoramento de metais pesados em águas, solos e sedimentos são extremamente importantes para controle ambiental. Neste trabalho determinaram-se as concentrações e disponibilidade de íons metálicos poluentes originados de várias fontes e sua dispersão em diferentes locais ao longo do Córrego da Anta - nordeste do Município de S. J. do Rio Preto, SP - drenagem do Rio Preto, inserido na Bacia Hidrográfica do Turvo/Grande. Este estudo baseou-se na identificação e quantificação de espécies químicas de metais utilizando diferentes reagentes ou extratores (extração seqüencial). ABSTRACT Most of the previous studies have been limited only to the determination of the total concentration of metals. Nevertheless, total concentration donate do not provide suitable information about bioavailability of potential toxic elements, and speciation. The aim of this work was to determines heavy metal concentrations and availability of polluting metal ions originated from the variety of sources and their dispersion along the Anta's Stream - Northeast of S. J. of Rio Preto state of São Paulo in one drainage slope of Rio Preto River, inserted in Turvo/Grande watershed. So far, this study is based on the identification and quantification of chemical species and fractionation of metals using different reagents or extracts (sequential extraction).